Murder Strategy and Achievement Motivation Upon Students' Reading Comprehension - Lalu Suparman (LP2M STIT Palapa Nusantara, 2015)
The investigation of this study was the effect of MURDER strategy and achievement motivation toward students'reading comprehension at the third graders of Madrasah Aliyah NW Penendem. The design of this study was post-test only control group design. The samples were taken by using the technique of random sampling which involved 80 students. The samples were divided into experimental and control group. The data were collected and administrated using questionnaire and test, which were analyzed using two-ways ANOVA. The results of the study displayed that (1) there is a significant difference on the English reading comprehension between the students who are taught by using MURDER strategy and those who are teught by using conventional strategy (FA=32.3, p 0.05).